Road Transport is the Main Source of Environmental Pollution - Rakhimovich, Shukurov Nuritdin (International Journal on Orange Technologies, 2023)
Recently, the most pressing problems of megacities is air pollution by road transport, as one of the most important elements of the functioning of the city. The article discusses the causes of air pollution by road transport, as well as ways and measures to reduce the concentration of harmful substances in the atmosphere.